The susceptibility to autoxidation of erythrocytes in diabetic mice: Effects of melatonin and pentoxifylline - Şekeroğlu, Mehmet Ramazan; Huyut, Zübeyir; Çokluk, Erdem; Özbek, Hanefi; Alp, Hamit Hakan (Wiley, 2017)
Oxidative stress had a great importance in development of complications in diabetes. We investigated effects of melatonin and pentoxifylline in diabetic mice. Swiss albino mice (n=40) were divided into four groups: alloxan-induced diabetes mellitus (DM), alloxan-induced diabetes with melatonin supplementation (DM+MLT), alloxan-induced diabetes with pentoxifylline supplementation (DM+PTX), and control. Glutathione-peroxidase (GSH-Px) activity, malondialdehyde (MDA) and reduced glutathione (GSH) levels, and susceptibility to oxidation of erythrocytes were measured. MDA levels were higher than control in the DM and DM+MLT. The DM had more MDA level than the DM+MLT and DM+PTX (P<0.001). After in vitro oxidation, MDA levels of all groups were found higher than the control. However, they were significantly lower than the DM in DM+PTX and DM+MLT (P<0.001). Although GSH levels of the DM and DM+PTX were less than the control, GSH-Px activity of the DM was lower than the control and DM+PTX (P<0.05). We suggest that there is increased oxidative stress and compromised antioxidant status of erythrocytes in diabetes; however, it can be effectively prevented by melatonin or pentoxifylline supplementation.
WOS: 000417915400004
Keywords: Antioxidant Enzymes; Diabetes; Melatonin; Pentoxifylline; RBC